Ingestão proteica avaliada por meio do registro alimentar de 24 horas e da recomendação proteica comparadas à excreção de nitrogênio urinário de 24 horas em pacientes com doença renal crônica em tratamento conservador - Juliana Meneghin de Melo (2013)
Introduction: The main dietary manipulation used to slow the progression of chronic kidney disease (CKD) is the restriction of proteins. Therefore, it is important to effectively control the protein intake of patients with progressive loss of renal function. Objective: To analyze the use of dietary records (DR) to evaluate the protein intake of patients with CKD on conservative treatment, considering the protein equivalent of urea nitrogen appearance (PNA) as the reference method. Methodology: the medical records of adult patients undergoing nutritional counseling at Nephrology and Nutrition Healthcare Service of Hospital das Clínicas, Federal University of Minas Gerais were evaluated from January 2009 to December 2011. Clinical, epidemiological, anthropometric and biochemical as well as dietary data were collected from the medical records and the anamnesis chart of the service. Protein intake estimated by the DR was compared to values of PNA at two different times, both referring to the same day of evaluation. Results: out of 45 patients included in the study, 23 (51.1%) were male and 25 patients (55.6%) were older than 60 years. The average education was 5.62 ± 3.73 years of study. Twenty-seven patients (60%) had increased body mass index. There was no significant difference in muscle and fat mass in the two times of evaluation in relation to age and sex. There was no correlation between the assessment of protein intake by DR and PNA in the two times of evaluation (Pearson correlation test, r = 0.06 and p = 0.69 and r = 0.15 and p = 0.32, respectively). The average caloric intake estimated by DR was lower than recommended in the two times of evaluation. Conclusion: in our sample there was no correlation between DR and the reference method PNA to assess protein intake in CKD patients on conservative treatment.